Nation & citizen in the Dominican Republic, 1880-1916 - Martínez Vergne, Teresita (University of North Carolina Press, 2005)
Combining intellectual and social history, this book explores the processes by which people in the Dominican Republic began to hammer out a common sense of purpose and a modern national identity, at the end of the nineteenth and beginning of the twentieth centuries.